The fourier analysis of ferromagnetic hysteresis properties in two dimensional ising model - Kanchiang K. (2014)
This work performed Monte Carlo simulation of ferromagnetic Ising spins in 2 dimensions to investigate the hysteresis properties, of both symmetric and asymmetric types, under the effects of external perturbations using the Fourier analysis. The hysteresis loops were analyzed using the discrete Fourier transformation. From the results, the hysteresis areas of both symmetric and asymmetric hysteresis depend on the amplitude of magnetic field and the Fourier coefficient of the first harmonic of real part. Nevertheless, the remnant magnetization of symmetric hysteresis depends only on the Fourier coefficients of odd harmonics of real part, while that of asymmetric hysteresis depends on both the Fourier coefficients of the zero and odd harmonics of real part. Additionally, the coercive field of symmetric hysteresis depends on the amplitude of magnetic field and the Fourier coefficients of the first harmonics of both real and imaginary parts. This suggests that the hysteresis behavior can be classified and modeled in frequency domain using the Fourier analysis. Copyright © Taylor &Francis Group, LLC.